عہدِسلاطین ِدہلی میں منصبِ شیخ الاسلام: The Position of Shaykh-ul-Islam in the age of Sultāns of Dehlī (Al-Qamar, 2021)
Holy Prophet PBUH is a great leader and mentor for all human being. After demise of the Holy Prophet this presumption of guideline of all human bein g is on the shoulders of His inheritors from  "Ulama". In Islamic world where other "Ulama"  performed their duties to provide line of action in novation and renewal of religious affairs to all Muslim "Ummah" as well as fulfilled the duty in Sub-continent in the era of "Salāteen-e-Delhi".They established a designation of "Shaikh-ul-Islam" to protect the religious affairs and implement the legitimate orders. This department was very effective to eliminate the nonreligious and apostasy matters.  The present study tries to explore the dynamics role, authorities, responsibilities and services of those "Ulama" who appointed as a "Shaikh-ul-Islam" by "Salāteen-e-Delhi". Epoch of "Sultanat-e-Delhi" is encompassing three years and above. In this research it will be demarcated and discussed about those rulers. whose Capital imperium was Delhi,and comprising in five families, Khāndān-e-Ghulāmān,Khāndān–e-Khilji, Khāndān_e_Sadāt and Khāndān-e-Lūdhi.
Keywords: Shaikh-ul-Islām; Delhi; Government; Muslim Era; Sub Continent; Sultān; Islam Values